Pesta Suka Cita dalam Kematian: Peran Adat dan Kehormatan dalam Upacara Saur Matua - Nathania Yosefin Siburian; Putri Dianeta Sinaga; Dedi Wilson Purba; Immanuel Silaban (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to understand the meaning and symbolism of the saur matua ceremony performed by the Batak Toba community, as well as to explore how this tradition reflects the cultural values ​​of the Batak community, such as hamoraon (wealth), hagabeon (many descendants), and hasangapon (honor). The method used in this study is a descriptive qualitative approach, with data collection techniques through in-depth interviews and documentation studies. Interviews were conducted with informants who are experienced in carrying out the saur matua ceremony, as well as literature studies relevant to the research topic. The collected data were analyzed thematically, to identify the main elements in the saur matua ceremony and understand its meaning in the context of the social and cultural life of the Batak Toba. The results of the study show that the saur matua ceremony is not just a death ritual, but a celebration of a person's success in life. Death is seen as an achievement, where the deceased is considered to have succeeded in fulfilling customary expectations in social, material, and descendant aspects. This ceremony reflects a view of life that values ​​honor and kinship, and provides a new meaning to a joyful death.